Including explicitly the question of 'which' in evaluation studies - Mohamadali, Noor Azizah; Garibaldi, Jonathan (2012)
Existing studies of user acceptance factors try to provide answers to the questions of ‘why’, ‘what’, ‘who’, ‘when’ and ‘how’. In this paper, we propose to include the explicit question of ‘which’ into future evaluation studies. Two distinct approaches are discussed to address the question of ‘which’. The aim is not to show which is the best, but rather to demonstrate the potential of some alternative approaches to addressing ‘which’.